A systematic review of the experiences of vulnerable people participating in research on sensitive topics. (December 2018) - Alexander, Susan; Pillay, Rona; Smith, Bronwyn
Abstract: Objective: The aim of this paper is to systematically review studies that discuss the experiences of vulnerable populations participating in research on sensitive topics. Design: Systematic review performed according to PRISMA guidelines. Data sources: Thirteen databases were searched, locating 197 articles. Following removal of duplicates, screening and full text review, 31 studies remained to be critically appraised. Review methods: As there was a mix of qualitative and quantitative articles, the Critical Appraisal Skills Program (CASP) toolkit and Effective Public Health Practice Project (EPHPP) tool were used to appraise the methodological quality of the articles. Following critical appraisal, the remaining 11 articles were synthesised narratively to identify common themes across the studies. Results: Despite some reports of distress, responses from participants were overwhelmingly positive. There was a strong link between symptomatology and potential for distress; however, the majority of those who did experience some level of discomfort stated they would still participate in future research. Three major themes were extracted: "It was worth it"; "Even if it hurt, I would do it again" and "Risk or benefit: fixing the location on the continuum". Conclusion: Although researchers frequently experience obstacles and the phenomenon known as "gatekeeping" when attempting to conduct research amongst vulnerable populations, there is little evidence of harm to participants. On the contrary, there is evidence of benefit for participants and evidence that they are willing to participate if given the opportunity. Although well-meaning, the actions of gatekeepers are not only paternalistic, they could be further marginalising vulnerable populations by denying them the benefits to be gained from research designed to identify and begin addressing their needs.